Cultura sertânica e currículo: diálogo fundante para a Educação no/do Campo numa escola pública municipal de Tucano/BA - Silva, Maria José Firmino da (2013)
This case study aimed to answer the following research question: how are the relations between the curriculum proposed by the Cristóvão Colombo School and the sociocultural contexts of their students from the perspective of Rural Education? So, considering these relations as dense, complex, opaque and adversarial, we chose a qualitative approach, referenced in Ethno Critical research that enabled us to understand the ways of the people to make sense and submit their everyday issues, from the social place which they speak . In this perspective of the social place, in the data analysis we were inspired in some assumptions of Discourse Analysis (ORLANDI, 2003, 2006, 2012). Our locus of research, so, was a Municipal Public school of Tucano / Ba and the collaborator subjects were seven teachers, the educational coordinator and the head mistress of the institution and nineteen students. To form the corpus of this work, we conducted interviews, focus groups, document analysis, observations and photographs that enabled us, in open-ended considerations, to understand that the relationship between the curriculum proposed by the Cristóvão Colombo School and the sociocultural contexts of their students are configured, mainly, through pedagogical projects as well as the dialogue between the knowledge contained in textbooks and the reference contexts of the students, but almost always spontaneously, without registration and without intentionality.